Metacognitive Awareness Based on Gender in Conceptual Change Learning Assisted Android Mobile-learning on the Topic of the Human Reproductive System - Wiono, Wisnu Juli; Dewi, Safira Permata (Universitas Lampung, 2023)
Abstract: Metacognitive Awareness Based on Gender in Conceptual Change Learning Assisted Android Mobile-learning on the Topic of the Human Reproductive System. This study aims to describe the level of metacognitive awareness of male and female students in conceptual change learning on the topic of the human reproductive system, the relationship between knowledge about cognition and cognitive regulation. The research subjects were students of class XI at a high school in Bandar Lampung. The instrument used to collect data is a metacognitive awareness questionnaire developed by Schraw & Dennison (1996). The results of the study show that male and female students are dominantly at the level of